The Effect Of Relaxation Education To Reduce Pain In Post-Operative Patients - Ernawati, Naya; Marsaid, Marsaid; Ciptaningtyas , Maria Diah; Sulastyawati, Sulastyawati; Astuti, Erlina Suci; Wiyono, Joko; Ugsang Acob, Joel Rey (Inovasi Lokal, 2024)
Pain can provide a peripheral vasoconstriction response which causes blood pressure and pulse to rise. Providing relaxation to post-operative patients can reduce post-operative pain. Relaxation education often proves effective in reducing pain levels in post-operative patients. Relaxation techniques such as deep breathing, meditation, and visualization can help reduce the physical and emotional tension that is often associated with pain. Apart from reducing physical pain, relaxation education can also improve the patient's psychological well-being. Patients can feel calmer, better able to deal with stress, and better able to control reactions to pain. By reducing pain levels, patients may require smaller amounts of pain medication or may not need medication at all. This can reduce the risk of side effects from painkillers and speed up the patient's recovery. By reducing pain and stress levels, relaxation education can help speed up the recovery process for post-operative patients. After this community service activity, patients feel more comfortable and are better able to move, which can help reduce the risk of post-operative complications.